Defining Financial Stability - Schinasi, Garry (IMF Working Papers; Working Paper ;, 2004)
The main objective of this paper is to propose a definition of financial stability that has some practical and operational relevance. Financial stability is defined in terms of its ability to facilitate and enhance economic processes, manage risks, and absorb shocks. Moreover, financial stability is considered a continuum: changeable over time and consistent with multiple combinations of the constituent elements of finance. The paper also discusses several practical implications of the definition that should be considered when using it for policy analysis or developing an analytical framework.